2017
DOI: 10.1590/1983-21252017v30n222rc
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Characterization and Sedimentological Responses of Watersheds With Different Land Uses to Precipitation in the Semiarid Region of Brazil

Abstract: -The objective of this work was to evaluated the precipitation characteristics (depth, I30 and erosivity) and their effects on sediment production in three watersheds under different managements of land use 35-year regenerating Caatinga (RC), thinned Caatinga (TC), which underwent thinning of trees with diameter smaller than 10 cm; and deforested Caatinga (followed by burning and pasture) (DC). The experimente was conducted in the central, tropical semiarid region of the State of Ceará, Brazil. The precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Mulch minimizes the impact rain has on soil surfaces [7], which might contribute to improved soil fertility, increase water availability through enhancing infiltration, and reduce evaporation, thus minimizing nutrient losses and also controlling soil temperature variations [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Mulch minimizes the impact rain has on soil surfaces [7], which might contribute to improved soil fertility, increase water availability through enhancing infiltration, and reduce evaporation, thus minimizing nutrient losses and also controlling soil temperature variations [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Isso demonstra que a CR não obteve características que aproximam a perda de água da CP, no entanto conseguiu características que favorecem a diminuição da produção de sedimentos. Ribeiro Filho et al (2017), estudando o escoamento e perda de solo em caatinga regenerada durante cinco anos, observaram que a mesma alcançou 23 eventos de escoamento e erosão, contra 18 de um caatinga manejada. A TA e a PD desempenharam o mesmo comportamento, aumentado a perda de solo em função da maior lâmina de escoamento, sendo a produção de sedimentos da TA muito superior às demais.…”
Section: Resultsunclassified
“…Although there is a close relationship between vegetation development and precipitated blades, in the area of the microbasin, there was an increase of 1,387 ha of exposed soil area, an increase of 218%, which may be related in part to anthropic actions. The results obtained by Zhou et al (2016) andRibeiro Filho et al (2017) in studies conducted in semiarid regions showed that a significant increase in exposed soil area occurs after the vegetation cover has been removed. However, such variation may also be related to distortion evidenced in the areas of "open caatinga" and "exposed soil" (Figure 4), as previously reported.…”
Section: Land Cover Classesmentioning
confidence: 99%
“…Erosion is responsible for the loss of 25 to 40 billion tons of soil per year, promoting the reduction in agricultural productivity and negatively impacting food security and the storage capacity of water and soil nutrients (Food and Agriculture Organization of the United Nations [FAO], 2015). The intensification of human activities in natural resources, mainly in semiarid regions, affects the physical properties of soil and the hydrological and sedimentological processes of river basins, such as water retention, runoff and sediment production (Prasannakumar, Vijith, Abinod, & Geetha, 2012;Ribeiro Filho, Palácio, Andrade, Santos, & Brasil, 2017).…”
Section: Introductionmentioning
confidence: 99%